Challenges and innovations for improving the sustainability of European agroforestry systems of high nature and cultural value: a stakeholder perspective - Rolo, Victor; Hartel, Tibor; Aviron, Stephanie; Berg, Staffan; Crous-Duran, Josep; Franca, Antonello; Mirck, Jaconette; Nunes Palma, Joao Henrique; Pantera, Anastasia; Paulo, Joana Amaral; Pulido, Fernando Javier; Seddaiu, Giovanna; et al. (Springer, 2020)
Traditional forms of agroforestry are often recognized as exemplar systems that successfully integrate food production, biodiversity conservation and high cultural values. However many traditional agroforestry systems in Europe are in decline or are threatened and the perspectives of local stakeholders on the production, management, socio-economic, and environmental dimensions of such systems are not fully understood. To fill this gap, we present results of participatory research performed with ten stakeholder groups (SG) across Europe to search for solutions to improve the economic and ecological sustainability of High Nature and Cultural Value agroforestry systems (HNCV agroforestry). Stakeholders included both users and beneficiaries of the HNCV agroforestry. First, SGs held open discussions (227 participants) to identify major challenges for the long-term sustainability of HNCV agroforestry. Challenges were classified into production, management, socio-economic and the environment categories. Second, they responded to structured questionnaires (120 respondents) that explored the positive and negative perceptions of 45 possible attributes of HNCV agroforestry. Third, innovative solutions were identified by individual and group discussions to address the four categories of challenge. Challenges were mostly identified for the management and socio-economic categories, but several challenges concerning production and environment were also pinpointed. Besides, solutions matched poorly with the challenges identified, and, while challenges were at some extent common across countries, solutions to address them were more case-specific. The successful implementation of these solutions requires an in-depth understanding of the diversity of socio-cultural and natural contexts of the HNCV agroforestry systems and building bottom-up proposals and collective actions based on this understanding. The sustainability of HNCV agroforestry would be benefited by providing farmers and managers with a financial advantage from the high nature and cultural value of these systems.
Keywords: Adaptive policy; European survey; Mosaic-like agriculture; Participative innovation; Regional-based solution; Silvopastoral systems